Getting the Word around: A Research Note on Communicating an Evangelistic Crusade - Swatos, William H. (Review of religious research, 1991)
This article reports on a four-wave telephone survey of households in a midwestern metropolitan area prior to, during, and after the staging of a Luis Palau evangelistic crusade in 1990. This social movement has some uniqueness in that it features a leader who is not a well-known figure and has no structure to build upon from the larger social system to insure participation. The findings show that the organizers of the event were successful in raising familiarity with Palau's name from less than ten to over forty percent of the population. Those from conservative Protestant backgrounds were most likely, as expected, to know of Palau, but as time passed Roman Catholics and nonmembers formed an increasing segment of those familiar with his name. Among the sources of information that were most effective in communicating crusade information, once an active advertising program was undertaken, were the newspapers, invitations hung on residence doors, and yard signs on supporters' homes and businesses.